The Concept of Ukhuwah Islamiyah in Building Civil Society for Generation Z - Verina Arti Kurnia Sari; Nasikhin; Mustopa (ARIMA : Jurnal Sosial Dan Humaniora, 2025)
This research aims to analyze the concept of Ukhuwah Islamiyah and its contribution in building civil society among Generation Z. The focus of the research includes Generation Z's understanding of the values of Ukhuwah Islamiyah as well as the challenges and opportunities in its application in the digital era. This study uses a qualitative method with a descriptive approach through literature studies, collecting secondary data from related scientific journals. The findings of the study show that Generation Z interprets Ukhuwah Islamiyah through a digital lens, integrating the values of brotherhood, justice, tolerance, and inclusivity in social life. These values are an important foundation in realizing a harmonious and just civil society. The study also identified challenges such as digital individualism and disinformation, as well as opportunities through social media and religious education platforms. As a contribution, this study provides strategic recommendations to increase the understanding and participation of Generation Z in actualizing Ukhuwah Islamiyah, as well as enriching academic studies on the relationship between Islamic values and the development of modern society.